Radical Mind, New Identity? Results From a Survey of the Youngest Voters on the Eve of 2023 Parliamentary Elections in Poland - Sula, Piotr; Błaszczyński, Kamil; Kuś, Michał; Kozdraś, Grzegorz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2025)
Paper offers a snapshot of the political preferences of youngest voters in Poland on the eve of parliamentary elections 2023, explaining it through prism of theory of socialisation and historical legacy. The study is based on the results of an empirical survey conducted in spring 2023 in two regions: Podkarpackie and Lubuskie. The results showed that the plurality (49%) of prospective first-time voters back the radical right-wing Confederation (Konfederacja). Its supporters were more numerous in Podkarpackie (53.2%) than in Lubuskie (42.5%) and more men (67.8%) than women (25.4%) declared support for Confederation. The gap between the Confederation and its nearest contender, Civic Platform/ Civic Coalition (Platforma Obywatelska/Koalicja Obywatelska – PO/KO), was immense, with PO/KO receiving the support of just 13.3% of prospective youngest voters. The potential voter share of the Law and Justice (Prawo i Sprawiedliwość – PiS) was even lower (7.8%). In this paper, we provide the characteristics of voters of each party by including ideological beliefs, civic activity and other demographic characteristics. We also provide an interpretation of the differences between the political preferences of youngest voters and the whole population, and the reasons for such a radical shift. Artykuł przedstawia obraz preferencji politycznych najmłodszych wyborców w Polsce tuż przed wyborami parlamentarnymi w 2023 roku, analizując je przez pryzmat teorii socjalizacji i dziedzictwa historycznego. Badanie opiera się na wynikach empirycznej ankiety przeprowadzonej wiosną 2023 roku w dwóch regionach: podkarpackim i lubuskim. Wyniki pokazały, że największa grupa (49%) potencjalnych pierwszorazowych wyborców popiera radykalnie prawicową Konfederację. Jej zwolennicy byli liczniejsi na Podkarpaciu (53,2%) niż w Lubuskiem (42,5%), a także wśród mężczyzn (67,8%) niż kobiet (25,4%). Przewaga Konfederacji nad jej najbliższym konkurentem – Platformą Obywatelską/Koalicją Obywatelską (PO/KO) – była ogromna, ponieważ PO/KO uzyskała poparcie jedynie 13,3% potencjalnych najmłodszych wyborców. Potencjalne poparcie dla Prawa i Sprawiedliwości (PiS) było jeszcze niższe i wyniosło 7,8%. W artykule przedstawiamy charakterystykę wyborców każdej z partii, uwzględniając przekonania ideologiczne, aktywność obywatelską oraz inne cechy demograficzne. Próbujemy również zinterpretować różnice między preferencjami politycznymi najmłodszych wyborców a całej populacji oraz przyczyny tak radykalnego przesunięcia.
Radykalny umysł, nowa tożsamość? Wyniki badania najmłodszych wyborców w przededniu wyborów parlamentarnych w 2023 r. w Polsce
Keywords: youngest voters; Poland; political preferences; najmłodsi wyborcy; Polska; preferencje polityczne